Teaching about teaching sexuality and religion - Stephens, Darryl W. (Teaching theology and religion, 2017)
Classroom instructors implementing pedagogical strategies for embodied learning about sexuality and religion need institutional support and assistance from colleagues and mentors to be successful. One means of providing institutional and peer support for classroom instructors is to host and lead a pedagogy workshop. Building on the work of Ott and Stephens on embodied learning and other articles and teaching tactics found throughout this issue of Teaching Theology and Religion, this article presents a sample design for a two-hour workshop with faculty and/or graduate teaching assistants on the topic of teaching sexuality and religion. Non-expert facilitators can lead this workshop and it is intended to start a conversation about pedagogy rather than to provide definitive answers to end the discussion. The goals are to demystify a taboo topic and to provide concrete strategies for teaching that will promote responsible engagement and a better-integrated learning experience for students.